Multidisciplinary approach for repeat musculoskeletal lesion biopsy after nondiagnostic initial sampling: A 10‐year single‐center experience. Issue 1 (13th October 2020) - Abboud, Salim; Kosaraju, Vijaya; Bhatt, Aashish; Egler, Rachel; Elliott, Robin; Faraji, Navid; Mangla, Ankit; Mansur, David; Rothermel, Luke; Saab, Shahrazad; Young, Peter; Getty, Patrick; et al.
Abstract: Background and Objectives: Success rates for initial image‐guided biopsy of musculoskeletal (MSK) lesions have been well documented; evidence regarding success rates for repeat biopsy following initially nondiagnostic (ND) image‐guided biopsy of MSK lesions is more limited. This study evaluates the outcomes of repeat computerized tomography‐guided MSK biopsies following ND biopsies using a multidisciplinary approach. Materials and Methods: Electronic medical record search covering a 10‐year period identified patients that received two or more biopsies for an MSK tumor or tumor‐like process. The decision for initial and repeat image‐guided biopsy of each lesion was made following multidisciplinary MSK tumor board review. Lesion location, histopathology results, size of biopsy needle when available, and change in technique between biopsy attempts was documented. Results: Repeat biopsy rate was 1.6%. 23 patients with repeat MSK biopsy were identified. A total of 17 of 23 (74%) repeat biopsy attempts were diagnostic. A total of 22 of 23 (96%) repeat biopsy attempts were clinically useful. Diagnostic repeat biopsies were described as employing one or more of five technical differences compared to the first biopsy attempt, the most common being improved targeting of the lesion itself. Conclusions: A multidisciplinary approach may yield improved repeat‐biopsy rates and clinical utility of repeat MSK biopsies compared to prior reports.